How do different motives for R&D cooperation affect firm performance? An analysis based on Swiss micro data - Spyros Arvanitis (ETH Zurich, KOF Swiss Economic Institute, 2009)
Starting point of our analysis is the empirical fact that firms pursue different goals when getting engaged in R&D collaborations, often more than one goal at the same time. Given that firms are driven by different motives for R&D cooperation, the aim of this article is to investigate the differences related to different motives with respect (a) to the factors influencing the likelihood of R&D cooperation as postulated by theory; and (b) to the impact of R&D cooperation on firm innovativeness and firm productivity. On the whole, distinguishing various cooperation motives appears to be fruitful because it allows more differentiated insights with respect to the importance of factors determining cooperation that would remain hidden behind the overall variable R&D cooperation yes/no. Not only R&D cooperation in general but also cooperation driven by each of the seven motives considered in this paper correlate positively with the sales share of innovative products. With respect to innovativeness the characterization of cooperation by the driving motive did not add much more insights that it could be gained through the overall variable R&D cooperation yes/no. Technology-motivated collaborative activities show a weaker tendency to positive direct effects on productivity than cost-motivated cooperation. In this case, the distinction of several cooperation motives yields some additional insights as compared to the overall cooperation variable.
Keywords: O30; 330; R&D cooperation; absorptive capacity; incoming spillovers; innovation; Betriebliche Forschung; Investition; Auslandsniederlassung; Spillover-Effekt; Innovationsdiffusion; Unternehmensentwicklung; Schweiz